Exposure to non-core foods and beverages in the first year of life: Results from a cohort study - Koh, G.; Scott, J.; Oddy, W.; Graham, Kathleen; Binns, Colin (Wiley-Blackwell Publishing Asia, 2010)
Aim: To report the proportion of Australian infants who were introduced to non-core foods and beverages and to identify factors that are associated with the introduction of non-core foods and beverages to infants in the first year of life. Methods: Participants were 587 women recruited from two maternity hospitals in Perth and followed up by telephone interview at 4, 10, 16, 22, 32, 40 and 52 weeks post-partum to collect information on infant feeding practices. Factors associated with introduction of non-core foods and beverages by 52 weeks post-partum were identified using multivariate logistic regression.Results: The three non-core foods most commonly introduced to infants by 52 weeks post-partum were biscuits and cakes (91.6%, n = 415), hot chips/French fries (78.6%, n = 356) and ice-cream (68.2%, n = 309). Independent predictors of introduction of non-core foods and beverages by 52 weeks post-partum were age at which solids were first introduced and the presence of older siblings. Conclusion: Identifying factors associated with the introduction of non-core foods and beverages to infants is important to help health professionals better target early feeding interventions. Consistent recommendations are required to ensure clear understanding of what foods are suitable and not suitable for infants.